THE EFFECTIVENESS OF DISTRACTION TECHNIQUES FOR CHILDREN UNDERGOING SURGERY ON REDUCING THEIR PERIOPERATIVE ANXIETY AND POSTOPERATIVE PAIN AND THEIR PARENTS’ PREOPERATIVE ANXIETY: A SYSTEMATIC REVIEW AND META-ANALYSIS - SYAHZARIN BIN DAUD (2021)
Bachelor's